Предмет: Алгебра,
автор: nynz
упростить (3х-х^2\x^2-6x+9+2x\2x+5)умножить на (2х^2-x-15)=
Приложения:
Ответы
Автор ответа:
4
((3x-x^2)/(x^2-6x+9)+2x/(2x+5))*(2x^2-x-15)=-11x
1). (3x-x^2)/(x^2-6x+9)=(x(3-x))/((x-3)(x-3))=(x(3-x))(-(3-x)(x-3))=x/(-(x-3))
2). 2x/(2x+5)+x/(-(x-3))= (-2x(x-3)+x(2x+5))/(-(2x+5)(x-3))= (-2x^2+6x+2x^2+5x)/(-(2x^2-6x+5x-15))= 11x/(-(2x-x-15))
3). 11x/(-(2x^2-x-15))*(2x^2-x-15)=-11x
1). (3x-x^2)/(x^2-6x+9)=(x(3-x))/((x-3)(x-3))=(x(3-x))(-(3-x)(x-3))=x/(-(x-3))
2). 2x/(2x+5)+x/(-(x-3))= (-2x(x-3)+x(2x+5))/(-(2x+5)(x-3))= (-2x^2+6x+2x^2+5x)/(-(2x^2-6x+5x-15))= 11x/(-(2x-x-15))
3). 11x/(-(2x^2-x-15))*(2x^2-x-15)=-11x
Похожие вопросы
Предмет: Английский язык,
автор: GoodDayES
Предмет: История,
автор: Аноним
Предмет: Обществознание,
автор: esizov300
Предмет: Математика,
автор: SnowVolf
Предмет: Химия,
автор: isulli